Fuel cell and hydrogen storage development for a wheel chair - Rangel, C. M. (2010)
In this paper are presented, the recent advances of a demonstration project that focuses on the implementation of a hybrid system for a wheel chair incorporating a fuel cell and a metal hydride hydrogen storage system. Advantages regarding weight reduction and greater autonomy are emphasized, apart from the use of clean energy and the drastic reduction in charging time, when compared with the system before conversion.